Rise of the auto industry in China and its impact on European auto industry - Palička, Marek; Jaklová, Martina L.; Juppa, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
This thesis deals with the internationalisation strategies of Chinese car manufacturers towards the European car market in the period 2012-2025. It starts by introducing the internationalisation framework on a theoretical level with special regards to the automotive industry. In the second part then the major characteristics of the Chinese and European car markets are identified. The conclusions from this analysis then create the base for a subsequent analysis of capabilities of Chinese car manufacturers with respect to the target European market. In the last part of the paper the identified information is used for coming up with potential entry strategies of Chinese carmakers in Europe in the specified time period as well as identifying the most probable consequences of this market entry for the current market players.
Vedoucí práce: Martina L. Jaklová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses